Extended Petri Net Processor for Embedded Systems - Ventre, Luis Orlando (2020)
The evolution of technology and electronic devices, the wide-spread use of IoT, and the compliance with specific regulatory requirements of the industry have made the process of designing embedded systems more complex and challenging. These systems are generally parallel, concurrent, reactive, and/or event-driven. In these systems, the data and events are heterogeneous and non-deterministic as they interact with the external environment. Extended Petri nets constitute an elective platform and system-independent modeling language, which makes it appropriate for modeling embedded systems. To take full advantage of the modeling efforts, it is desirable to use the built models to obtain part of the system implementation. This paper presents the design and implementation of an Extended Petri Processor and its modular architecture. This processor makes use of the extended state equation of Petri Nets, executing the model of the mentioned systems, intending to mitigate the time needed for development, and to reduce programming errors.